2019
DOI: 10.1002/cnma.201800487
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Peroxidase Mimetic Activity of Porous Iron Oxide Nanoflakes

Abstract: Porous nanomaterials with superior peroxidase mimetic activity (nanozyme) at room temperature have gained increasing attention as potential alternatives to natural peroxidase enzymes. Herein, we report the application of porous iron oxide nanoflakes (IONFs), synthesized using the combination of solvothermal method and high-temperature calcination as peroxidase nanozyme for the oxidation of 3,3',5,5'-tetramethylbenzidine (TMB) in the presence of H 2 O 2 . The four IONF catalysts possess porous structures with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 43 publications
0
45
0
Order By: Relevance
“…The initial reaction velocity was calculated by Beer-Lambert Law. [27] The apparent kinetic parameters (K m and V max ) for both TMB and H 2 O 2 were estimated by using the Michaelis-Menten and the Lineweaver-Burk equations as outlined in our previous papers for studying enzyme-like activity of goldloaded nanoporous ferric oxide nanocubes, [6,10] porous iron oxide nanoflakes, [5] mesoporous nanocrystalline αor γ-iron oxide, [9] and mesoporous iron oxide. [11]…”
Section: Michaelis-menten Kinetic Parametersmentioning
confidence: 99%
See 3 more Smart Citations
“…The initial reaction velocity was calculated by Beer-Lambert Law. [27] The apparent kinetic parameters (K m and V max ) for both TMB and H 2 O 2 were estimated by using the Michaelis-Menten and the Lineweaver-Burk equations as outlined in our previous papers for studying enzyme-like activity of goldloaded nanoporous ferric oxide nanocubes, [6,10] porous iron oxide nanoflakes, [5] mesoporous nanocrystalline αor γ-iron oxide, [9] and mesoporous iron oxide. [11]…”
Section: Michaelis-menten Kinetic Parametersmentioning
confidence: 99%
“…Catalysis of TMB by natural peroxidases like HRP, as well as peroxidase mimicking nanozymes, in the presence of H 2 O 2 generates a blue colored 1-electron oxidation product (TMB ox ) which absorbs light at 652 nm and can be used for naked eye evaluation (qualitative) as well as UV-visible (UV-vis) quantification of the reaction. [5,6,9,10] Addition of strong acids to the reaction generates the yellow colored diimine terminal oxidation product which absorbs light at 450 nm and is electroactive. This yellow colored terminal reaction product can be used for UV-vis (semiquantitative, colorimetric), as well as electrochemical quantification.…”
Section: Peroxidase-like Activity Of Pom Nanomaterialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucose sensing was also achieved through the glucose-GOx reaction with good selectivity amongst other bioactive compounds. Tanaka et al started from Fe 3+ -glycerate precursor and applied thermal treatment to obtain porous Fe 2 O 3 flakes [145]. It was found that lower pyrolysis temperatures resulted in better Fenton-type activity for the synthesized Fe 2 O 3 , since those products had higher surface area and higher hexagonal α-Fe 2 O 3 content with more active sites compared to cubic γ-Fe 2 O 3 ( Table 1).…”
Section: Miscellaneous Structuresmentioning
confidence: 99%